Answer:
<em>x</em><em> </em><em>=</em><em> </em><em>4</em><em>5</em>
<em>y</em><em> </em><em>=</em><em> </em><em>5</em>
Step-by-step explanation:
<em>it</em><em> </em><em>is</em><em> </em><em>b</em><em>ecause</em>
<em>9</em><em>0</em><em>/</em><em>2</em><em> </em><em>=</em><em> </em><em>4</em><em>5</em>
<em>(</em><em>9</em><em>0</em><em>+</em><em>1</em><em>0</em><em>)</em><em>/</em><em>2</em><em>0</em><em> </em>
<em>(</em><em>1</em><em>0</em><em>0</em><em>)</em><em>/</em><em>2</em><em>0</em><em> </em><em>=</em><em> </em><em>,</em><em>5</em>